The Development of Canada's Five Leading National Ports - Forward, Charles (Urban History Review / Revue d'histoire urbaine, 1982)
The east coast ports of Montreal, Quebec, Saint John and Halifax, together with Vancouver on the west coast, have functioned as Canada's leading general cargo ports throughout much of the nation's history. Both competitive and complementary relationships have existed between them at various times, and the relative importance of each port has fluctuated in response to changes in transport technology and trading patterns. Before Confederation, Quebec was the leading port, but it soon lost this leadership to Montreal, as the steamship displaced the sailing vessel and the St. Lawrence Ship Channel was widened and deepened. Montreal dominated Canada's shipping trade for many decades until the recent rise of Vancouver finally overshadowed it. During their lengthy history all five ports have managed to survive periods of adversity and maintain their importance and respective roles in the nation's shipping trade, despite the appearance of many new competitors.